Melanistic leopards reveal their spots: Infrared camera traps provide a population density estimate of leopards in malaysia. Issue 5 (26th May 2015) - Hedges, Laurie; Lam, Wai Yee; Campos‐Arceiz, Ahimsa; Rayan, D. Mark; Laurance, William F.; Latham, Chris J.; Saaban, Salman; Clements, Gopalasamy Reuben
ABSTRACT To date, leopards (Panthera pardus) in Peninsular Malaysia have been overlooked by large carnivore researchers. This is in part due to the country's unique population of individuals that are almost all melanistic, which makes it nearly impossible to identify individuals using camera traps for estimating leopard density. We discovered a novel modification to infrared flash camera traps, which forces the camera into night mode, that allows us to consistently and clearly see the spots of a melanistic leopard. The aim of this project was 1) to determine the feasibility of identifying melanistic leopards with confidence using infrared flash camera traps, and 2) to establish a density estimate for the leopard population in a wildlife corridor in Malaysia using maximum likelihood and Bayesian spatially explicit capture‐recapture (SECR) models. Both SECR approaches yielded a leopard density of approximately 3 individuals/100 km2. Our estimates represent the first density estimate of leopards in Malaysia and arguably, the world's first successful attempt to estimate the population size of a species with melanistic phenotypes. Because we have demonstrated that melanistic leopards can be monitored with confidence using infrared cameras, future studies should employ our approach instead of relying on scars or body shape for identification. Ultimately, our approach can facilitate more accurate assessments of leopard population trends, particularly in regions where melanistic phenotypes largely occur. © 2015 The Wildlife Society.